Hypoglycemic activity and the activation of phosphorylation of a triterpenoid-rich extract from Euryale shell on streptozotocin-induced diabetic mice (Bangladesh Journal of Pharmacology, 2013)
In the present study, we examined the hypoglycemic properties and the effective mechanisms of a triterpenoid-rich extract from the Euryale shell (ES) in streptozotocin-induced (STZ) diabetic mice. The hydroalcoholic extract of ES (200, 400 and 600 mg/kg/day) was orally administered to STZ-diabetic mice for 4 weeks. We observed that in the liver of diabetic mice, the ES extract caused a sharp reduction in the gene expression of protein tyrosine phosphatase-1B (PTP1B) but induced the gene expression of phosphatidyl-inositol-3-kinase (PI-3K) and protein kinase B (PKB) compared with that of untreated diabetic mice. Additionally, a significant increase in the phosphorylation of the PKB protein was observed (p